2009
DOI: 10.1183/09031936.00073409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of home support and ventilator malfunction in 1,211 ventilator-dependent patients

Abstract: Risk management is an important aspect of home ventilation (HV). We examined the nature of calls to a home support helpline to identify patient/equipment problems and strategies to minimise risk for patients, healthcare teams and manufacturers.From 1,211 adult and paediatric patients with neuromuscular disease, chronic obstructive pulmonary disease or chest wall disease receiving HV, all calls to a dedicated respiratory support telephone hotline between January 1, 2006 and June 30, 2006 were analysed.1,199 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 13 publications
0
60
0
2
Order By: Relevance
“…24 Issues relating to ventilator equipment failure are not infrequent. In the United Kingdom, Chatwin and colleagues 25 reported on 1,211 ventilator-assisted individuals receiving NIV over a 6-month time frame and found an 8% failure rate per NIV device manufacturer, with higher failure rates in highly ventilator-dependent individuals and older devices. An earlier study of mostly tracheostomized ventilatorassisted individuals reported 189 equipment-associated issues in 150 users over 1 y and found that 43% were due to improper use or care of equipment by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…24 Issues relating to ventilator equipment failure are not infrequent. In the United Kingdom, Chatwin and colleagues 25 reported on 1,211 ventilator-assisted individuals receiving NIV over a 6-month time frame and found an 8% failure rate per NIV device manufacturer, with higher failure rates in highly ventilator-dependent individuals and older devices. An earlier study of mostly tracheostomized ventilatorassisted individuals reported 189 equipment-associated issues in 150 users over 1 y and found that 43% were due to improper use or care of equipment by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In the present issue of the European Respiratory Journal, CHATWIN et al [1] present data on the call centre they established to support more than 1,000 patients on home respirators. The Respiratory Unit of the Royal Brompton Hospital (London, UK) serves a vast geographical area.…”
mentioning
confidence: 99%
“…These calls can be made for a number of reasons; from simple concerns such as asking for spare part replacement, to more disturbing ones such alarms coming on during the night or to a respirator becoming noisy all of a sudden, to very serious ones such as a respirator breakdown in a respirator dependent patient. CHATWIN et al [1] have recorded and analysed all calls received during a 6-month period, from a population of 1,211 patients, from paediatrics to geriatrics, who were followed up at their centre. All patients had had a training process within the Royal Brompton Hospital unit, and all patients or families were deemed able to understand the use of home respirators, adequately fit and assembly/disassembly the mask and interfaces, start and stop the machines, and even to unlock the settings in order to change them according to telephonic instructions if this was thought useful by the on-call personnel.…”
mentioning
confidence: 99%
See 2 more Smart Citations